Effects of Psychological Interventions on Depression Symptoms in Oncology Patients: A Systematic Review - Lapeikis, Ignas; Armonaitė, Ieva; Baranauskytė, Vakarė; Banienė, Irina (Acta medica Lituanica, 2026)
Background: Depression is one of the most common psychological comorbidities among cancer patients and contributes substantially to a reduced quality of life and impaired treatment adherence. A range of psychosocial interventions have been proposed to address depressive symptoms in oncology, but evidence across intervention types remains heterogeneous. Aim: To evaluate the effectiveness of psychological interventions in reducing depressive symptoms among cancer patients. Methods: A systematic search of PubMed, ScienceDirect, Web of Science, and Clinical Key databases was conducted for studies published between 2016 and 2026. Randomized controlled trials and controlled intervention studies assessing psychological interventions for depressive symptoms in adult cancer patients were included. Data on the study design, patient characteristics, intervention type, depression assessment scales, and outcomes were extracted. Due to heterogeneity in interventions and outcome measures, the findings were synthesised narratively. Results: Twenty studies met the inclusion criteria. Interventions included cognitive behavioural therapy (CBT), mindfulness-based interventions (MBIs), mindfulness-based stress reduction (MBSR), mindfulness-based cognitive therapy (MBCT), and positive psychology approaches. Most studies reported significant reductions in depressive symptoms measured by using validated scales such as PHQ-9, HADS, BDI, and SDS. CBT- and mindfulness-based approaches demonstrated the most consistent improvements, although several trials reported no significant differences compared with control groups. Conclusions: Psychological interventions, and particularly CBT- and mindfulness-based approaches, are associated with reductions in depressive symptoms among cancer patients. However, substantial heterogeneity in the intervention design and outcome reporting limits direct comparison across studies. Further large-scale randomized trials using standardised outcome measures are needed to establish optimal psychosocial treatment strategies in oncology.